2020
DOI: 10.1021/acs.langmuir.0c00995
|View full text |Cite
|
Sign up to set email alerts
|

Correction to “Molecular Simulations Shed Light on Potential Uses of Ultrasound in Nitrogen Adsorption Experiments”

Abstract: We found a mistake in our recent work. The mistake was made in the chemical potential at saturation calculation μ 0 *: we reported μ 0 * = −9.596, while the correct value should be −9.332. Therefore, Figures 1−4 and 6 should be replotted, and although the new ones have a similar trend, they have different numerical values. Our conclusions also remain the same. The black dashed vertical lines represent the values corresponding the old saturation chemical potential value. Table 2 is also revised.Langmuir pubs.ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 5 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…Though the differences between the adsorbates argon and nitrogen were not explicitly investigated in the publications of the group of Gor, a close look on their figures and data at (or near) the normal boiling points reveals some differences between the two adsorbates. For example, for pores with a diameter of 6 nm the enhancement of β ads is ≈50% for nitrogen 34 and ≈30% for argon. 19 However, an analysis of their results indicates that the absolute values for the enhancement are almost identical for argon and nitrogen, which contrasts somewhat to our experimental results.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Though the differences between the adsorbates argon and nitrogen were not explicitly investigated in the publications of the group of Gor, a close look on their figures and data at (or near) the normal boiling points reveals some differences between the two adsorbates. For example, for pores with a diameter of 6 nm the enhancement of β ads is ≈50% for nitrogen 34 and ≈30% for argon. 19 However, an analysis of their results indicates that the absolute values for the enhancement are almost identical for argon and nitrogen, which contrasts somewhat to our experimental results.…”
Section: Resultsmentioning
confidence: 99%
“…This possibility is the result of the vanishing shear modulus of the confined liquid nitrogen, and the method can also be applied for other adsorbates with a vanishing shear modulus like argon . The longitudinal modulus of the adsorbed liquid nitrogen was not explicitly calculated or considered by Warner and Beamish; however, Maximov and Gor , used this experimental study as starting point for a comparison with their molecular simulations. Warner and Beamish and Maximov and Gor , showed that the effective longitudinal modulus β of the sample jumps above the modulus of the empty sample, β 0 , as soon as the pores are completely saturated with liquid nitrogen.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations